Accuracy and User Performance Evaluation of a New, Wireless-enabled Blood Glucose Monitoring System That Links to a Smart Mobile Device. (July 2017) - Bailey, Timothy S.; Wallace, Jane F.; Pardo, Scott; Warchal-Windham, Mary Ellen; Harrison, Bern; Morin, Robert; Christiansen, Mark
Background: The new Contour ® Plus ONE blood glucose monitoring system (BGMS) features an easy-to-use, wireless-enabled blood glucose meter that links to a smart mobile device via Bluetooth ® connectivity and can sync with the Contour ™ Diabetes app on a smartphone or tablet. Methods: The accuracy of the new BGMS was assessed in 2 studies according to ISO 15197:2013 criteria. In Study 1 (laboratory study), fingertip capillary blood samples from 100 subjects were tested in duplicate using 3 test strip lots. In Study 2 (clinical study), 134 subjects with type 1 or type 2 diabetes enrolled at 2 clinical sites. BGMS results and YSI analyzer (YSI) reference results were compared for fingertip blood obtained by untrained subjects' self-testing and for study staff–obtained fingertip, subject palm, and venous results. Results: In Study 1, 99.0% (594/600) of combined results for all 3 test strip lots fulfilled ISO 15197:2013 Section 6.3 accuracy criteria. In Study 2, 99.2% (133/134) of subject-obtained capillary fingertip results, 99.2% (133/134) of study staff–obtained fingertip results, 99.2% (125/126) of subject-obtained palm results, and 100% (132/132) of study staff–obtained venous results met ISO 15197:2013 Section 8 accuracy criteria. Moreover, 95.5% (128/134) of subject-obtained fingertip self-test results were within ±10 mg/dl (±0.6 mmol/L) or ±10% of the YSI reference result. Questionnaire results showed that most subjects found the BGMS easy to use. Conclusions: The BGMS exceeded ISO 15197:2013 accuracy criteria both in the laboratory and in a clinical setting when used by untrained subjects with diabetes.